Pengaruh Pemasaran Digital dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan Studi Kasus pada INTAKO Sidoarjo - Hamid, Mas Ghoniyyul; M Mustaqim (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to analyze the influence of digital marketing and customer experience on customer loyalty at INTAKO Sidoarjo. The shift toward digital- based marketing has become a crucial approach for businesses in reaching consumers who are increasingly active in online spaces. On the other hand, a positive customer experience is believed to drive repeat purchases and foster long- term loyalty. This research uses a descriptive quantitative approach, employing a survey method by distributing questionnaires to 96 respondents who are INTAKO customers, whether shopping online or offline. The sampling technique used is accidental sampling. Data were analyzed using multiple linear regression through SPSS version 26. The results indicate that both digital marketing and customer experience have a positive and significant effect on customer loyalty, both partially and simultaneously. Among the two, customer experience is found to have the most dominant influence. These findings suggest that building customer loyalty is not solely dependent on the presence of digital platforms, but also on the quality of experience delivered in each customer interaction.